Angebotsökonomie: wenig Innovation – viele Jobs! - Alfred Kleinknecht (Wirtschaftsdienst, 2017)
– Deregulation of labour markets through structural reforms as proposed by supply side economists has a negative impact on innovation and brings down the growth rates of labour productivity. This paper discusses why the Schumpeter II innovation model is functioning poorly with higher labour turnover. Deregulation of labour markets also changes power relations between capital and labour, which leads to lower wage growth. Panel data analyses show that a one per cent lower wage increase leads to 0.32-0.49% lower growth of value added per labour hour.
Keywords: J53; K31; O31; 330